DNA inspired bi-directional Lempel-Ziv-like compression algorithms - Mahmood, Attiya; Islam, Nazia; Nigatu, Dawit; Henkel, Werner (2014 8th International Symposium on Turbo Codes and Iterative Information Processing (ISTC), 2014)
The bi-directional reading processes in DNA replication and gene expression together with the similarities between the so-called alternative splicing and Lempel-Ziv (LZ) algorithms has motivated us to incorporate bi-directional readings into LZ algorithms. LZ77, LZ78, and LZW84 are universal lossless data compression algorithms. A modified version of these algorithms that takes into account both forward and reverse readings is presented in this work. It is shown that bi-directional reading can improve the compression ratio at the expense of slight modifications in LZ algorithms provided that there exists some symmetry in the information content. Results are presented for text, image, and audio files.